Upaya Meningkatkan Hasil Kebugaran Jasmani Siswa Kelas IX-F SMP Negeri 30 Semarang Menggunakan Metode Pembelajaran Ular Tangga - Devan Gusty Darmawan, devan; Agus Wiyanto; Buyung Kusumawardhana; Hartini (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2025)
This research was motivated by the lack of knowledge about physical fitness activities and the low enthusiasm of Grade IX-F students in Physical Education (PE) classes at SMP Negeri 30 Semarang. The aim of this study was to examine the improvement in PE learning outcomes among ninth-grade junior high school students using a snake and ladder game-based learning model. This study employed a Classroom Action Research (CAR) method conducted in two cycles. The subjects of the study were 32 ninth-grade students. In the first cycle, the average class score was 77.2, with 25 students reaching the minimum mastery criteria (KKTP) and 7 students not yet achieving it, resulting in a mastery percentage of 78.1%. In the second cycle, there was an improvement in learning outcomes with an average class score of 87.2; 30 students achieved the KKTP and only 2 did not, resulting in a mastery percentage of 93.8%. These results indicate that the implementation of the snake and ladder game-based learning model can be used to improve students' learning outcomes.